Comparison study of URANS and hybrid RANS-LES models on predicting vertical axis wind turbine performance at low, medium and high tip speed ratio ranges. (May 2021) - Syawitri, T.P.; Yao, Y.F.; Chandra, B.; Yao, J.
Abstract: Comparison study of unsteady Reynolds-averaged Navier-Stokes (URANS) and hybrid RANS-LES models is carried out for predicting the performance of three-straight-bladed vertical axis wind turbine operating within tip speed ratios ( TSR s) ranges of (1.44–3.3). The evaluation is focused on power coefficient, moment coefficient and vortex structure generation, growth and transportation predictions. It was found that URANS turbulence modelling is sufficient for averaged power coefficient prediction and specific range of TSR evaluation, and it also benefits from short simulation run time. To further evaluate flow field details and to understand the underlying flow physics such as dynamic stall behaviour, hybrid RANS-LES turbulence modelling is necessary. Comparing between hybrid models adopted, stress-blended eddy simulation based on transition shear-stress transport (TSST) model has achieved an overall better performance, such as a reduction of simulation discrepancy by 50% in low TSR s range compared to TSST turbulence model. In both medium and high TSR s ranges, the modelling discrepancies are less than 3% compared to TSST turbulence models at about 25% extra computational time. Furthermore, in high TSR s range, hybrid RANS-LES models are able to predict the appearance of vortex shedding at high azimuthal angles (θ ≥ 180°) for which URANS models failed to capture. Highlights: Comprehensive analysis of URANS and hybrid RANS-LES CFD models for VAWT flow. Study focuses on turbine power, moment coefficient and aerodynamics prediction. Transition SST model is sufficient for overall performance prediction. Hybrid RANS-LES can perform better prediction of VAWT dynamic stall behaviour. SBES transitional SST generates more accurate predictions than other models.